Analysis of the offensive phase in elite soccer through observational methodology: A systematic review - Pueyo Romeo, Luis; Murillo Lorente, Víctor; Álvarez Medina, Javier; Amatria Jiménez, Mario (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This systematic review focused on analyzing the offensive phase of elite soccer using observational methodology, following the PRISMA guidelines for the collection and synthesis of existing literature. An exhaustive search was conducted in PubMed, Web of Science, and Scopus databases, selecting publications from January 2012 to December 2022, and with search terms such as tactical analysis, style, and gameplay patterns, among others. Furthermore, the GREOM guide was followed, which ensures a standard of quality in works carried out using observational methodology. Of the 1,114 articles identified, 68 met the criteria for inclusion in the final sample, which were taxonomically categorized according to their focus: player analysis, offensive tactics, goal analysis, set-piece actions, and the influence of contextual factors. The findings indicated that offensive efficacy in elite soccer is a complex phenomenon, resulting from the interaction between individual skills, team strategies, and adaptability to situational factors. This study concluded that offensive performance should be approached from a holistic perspective that considers the confluence of various variables for its comprehensive understanding.